Quality analysis of prescriptions of polymyxin B in a high-complexity public hospital (Revista Contexto & Saúde, 2023)
Objectives: The study proposed to evaluate the quality of polymyxin B prescription in a Brazilian high-complexity public teaching and reference hospital. Methods: This study of drug use describes the medical prescription habits, with the retrospective collection carried out with critically ill patients using polymyxin B. The dose by weight for each patient's first prescription was calculated from the Infectious Diseases Society of America (IDSA) guideline to assess the loading dose adequacy. The glomerular filtration rate (GFR) was estimated to evaluate the adequacy of the dose prescribed at the onset of treatment, based on the Kidney Disease – Improving Global Outcomes (KDIGO). Results: 346 prescriptions were analyzed, representing 259 patients. Only 61 (17.6%) included a loading dose of polymyxin B. On the other hand, no adjusted doses were identified in 147 (73.1%) prescriptions for patients whose GFR range requires renal adjustment. A total of 438 cultures were analyzed, and 97 carbapenem-resistant GNB were selected for the study (22.2%). A loading dose was identified in only 13 (13.4%) of these prescriptions, and 80 (82.5%) prescriptions had no dose adjustment by renal function. The prevalent microorganism was Klebsiella pneumoniae (70 [16.0%]). Conclusion: The study identified high rates of non-compliance with the protocol for using polymyxin B concerning the loading dose and a high percentage of cases in compliance with the protocol regarding the nonindication of renal adjustment. The development of institutional clinical protocols and the performance of the ASP team are critical to rationalizing the use and avoiding unsatisfactory clinical and microbiological results.
Keywords: agentes anti-infecciosos, resistência a medicamentos, farmacêutico clínico, serviços de controle de infecção, polimixina B.